A New Photovoltaic Blocks Mutualization System For Micro-Grids Using An Arduino Board And Labview - Abdelkader Mezouari; Rachid Elgouri; Mohammed Alareqi; Khalid Mateur; Hamad Dahou; Laamari Hlou (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The photovoltaic systems are often employed into micro-grids; Micro-grids are small power grids designed to provide a reliable and better power supply to a small number of consumers using renewable energy sources. This paper deals with DC micro-grids and present a new system of monitoring and sharing electricity between homes equipped with photovoltaic panels (PV) in the goal to reduce the electrical energy waste. The system is based on dynamic sharing of photovoltaic blocks through homes in stand-alone areas, using an arduino board for controlling the switching matrix. The LABVIEW program is used to further process and display collected data from the system in the PC screen. A small-scale prototype has been developed in a laboratory to proof the concept. This prototype demonstrates the feasibility and functionality of the system.